1998
DOI: 10.1016/s0886-3350(98)80224-1
|View full text |Cite
|
Sign up to set email alerts
|

Secondary closure of posterior continuous curvilinear capsulorhexis in normal eyes and eyes at risk for postoperative inflammation

Abstract: Reclosure of the PCCC occurred in both groups, although the frequency of reclosure was slightly higher in the inflammation group. Although PCCC does not prevent posterior capsule opacification in all cases, it is useful in specific situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 18 publications
2
30
0
3
Order By: Relevance
“…However, even this barrier may be overrun by LECs, occasionally resulting in a contiguous membrane occluding the PPCCC opening (posterior epithelial ongrowth), especially in eyes of young individuals and those at risk for developing postoperative inflammation. [8][9][10][11] A low capsulotomy rate reflects the absence of visiondisturbing PCO in the center. However, peripheral opacities may be significant.…”
mentioning
confidence: 99%
“…However, even this barrier may be overrun by LECs, occasionally resulting in a contiguous membrane occluding the PPCCC opening (posterior epithelial ongrowth), especially in eyes of young individuals and those at risk for developing postoperative inflammation. [8][9][10][11] A low capsulotomy rate reflects the absence of visiondisturbing PCO in the center. However, peripheral opacities may be significant.…”
mentioning
confidence: 99%
“…Surgical capsulotomy closure has also been reported in eyes at risk (uveitic, young adults). 10 We report spontaneous closure of a Nd:YAG posterior capsulotomy for capsular blockage syndrome 1 week post-surgery, requiring repeat capsulotomy. This may be due to phimosis, but more likely from LEC migration.…”
Section: Discussionmentioning
confidence: 94%
“…The disadvantage of a smaller PCCC is the visual axis obscuration caused by the proliferation of the lens epithelial cells from the PCCC margin. [22][23][24][25] The reported incidence of visual axis obscuration with PMMA IOLs is 60% to 100% when capsulotomy is not combined with anterior vitrectomy. 26 In our study, we reported that in children younger than 5 years who underwent PCCC without anterior vitrectomy using PMMA IOLs, 62.5% developed visual axis obscuration at an average follow-up of 13.3 months.…”
Section: Discussionmentioning
confidence: 99%